Micropropagation, Micromorphological Studies, and In Vitro Flowering in Rungia pectinata L. - Mahipal S. Shekhawat; M. Manokari; C. P. Ravindran (Scientifica)
A tissue culture protocol was developed for an important medicinal plant Rungia pectinata L. in the present study. Nodal shoots were used as explants and surface-sterilized with 0.1% HgCl2 solution. Murashige and Skoog (MS) medium was used to establish the cultures of R. pectinata. The bud break was reported on MS medium supplemented with 1.0 mg L−1 6-benzylaminopurine (BAP). About 98% response was observed with this media combination and maximum 3.2 shoots per explant with 4.3 cm length were recorded. The shoots were further multiplied using MS medium augmented with 0.5 mg L−1 each of BAP and kinetin (Kin) + 0.1 mg L−1 indole-3 acetic acid (IAA). Maximum 13.2 shoots per explant with 5.2 cm length were observed. All the shoots were rooted (4.9 roots per shoot with 3.5 cm length) on half strength MS medium fortified with 2.0 mg L−1 indole-3 butyric acid (IBA). In vitro flowering was induced from the shoots on half strength MS medium supplemented with same concentrations and combinations of growth regulators used for shoot multiplication under 12/12 hr light/dark photoperiod. The plantlets were hardened in the greenhouse for two months and finally transferred to the field. The foliar micromorphological studies revealed the developmental changes in stomata, vein density, and trichomes during the culture of shoots under in vitro conditions.